Analisis Faktor-Faktor Yang Mempengaruhi Perilaku Konsumen Dalam Membeli Daging Sapi (Studi Kasus : Di Pasar Petisah Kecamatan Medan Petisah Kota Medan) - Rahma Sari Siregar (JASc (Journal of Agribusiness Sciences), 2018)
Livestock sub-sector is part of the agricultural sector. Livestock sub-sector has a strategic role in the lives of human resource development as well as the Indonesian economy.  This role can be seen from the function of farm products as a provider of animal protein is essential for the development and growth of the human body.  One animal products that provide high protein are beef and also, has a relatively expensive price and demand for beef is also high, especially in Medan.The purpose of this study was  to determine the factors that influence consumer behavior in buying beef in the market district of Medan Petisah.  The sampling method is done by purposive sampling method.  Respondents in this study is the household customers who are buying beef in Petisah Market. Samples taken are as many as 60.  The data collected primary and secondary data.  The results showed that the factors that influence consumer behavior in buying beef is affected by the variable needs and situation of purchase, this can be seen from the t-test for the variable needs of consumers of beef amounted to 12 591 larger than t-table is 1671 and for situation variable purchase 3,483 t count larger than t-table is 1,671.